The Development and preliminary usability testing of a digital reproductive health education model for maternal preparedness in disaster-prone areas - Dini Afriani; Gita Arisara; Hana Fitria Andayani; Muhammad Agreindra Helmiawan (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2026)
Background: Pregnant women are particularly vulnerable during disasters because disruptions in healthcare services, limited access to reproductive health information, and inadequate disaster preparedness may compromise continuity of maternal care. Maternal health education and disaster-preparedness interventions are often delivered separately, highlighting the need for an integrated digital approach. Purpose: This study aimed to develop a digital reproductive health education model for maternal preparedness in disaster-prone areas and evaluate its preliminary usability among intended users. Methods: This study employed Type 1 Design and Development Research consisting of four phases: needs assessment, prototype design and development, expert evaluation and refinement, and preliminary usability testing. The needs assessment included a survey of 32 pregnant women and semi-structured interviews with five participants. Quantitative and qualitative findings from the needs assessment were integrated to inform the design requirements for the digital model. Four multidisciplinary experts evaluated the prototype, which underwent two revision cycles before preliminary usability testing with 10 pregnant women. Quantitative data were analyzed descriptively, while qualitative interview data were analyzed thematically. Results: The needs assessment identified limited disaster preparedness, barriers to maternal healthcare access during emergencies, and substantial educational needs. Four qualitative themes reflected uncertainty during disasters, difficulties accessing maternal healthcare, fragmented health information, and preference for an integrated digital platform. Based on these findings, a digital reproductive health education model named LERINA (Layanan Edukasi Kesehatan Reproduksi Tanggap Bencana) was developed, comprising six integrated modules: education, preparedness assessment, maternal monitoring, emergency support, consultation, and an administrative dashboard. Expert evaluation yielded mean scores of 4.74 for content and 4.78 for interface. Preliminary user testing demonstrated favorable usability, with an overall score of 4.71 ± 0.28. Conclusion: LERINA, a needs-informed digital reproductive health education model, was systematically developed and demonstrated favorable preliminary usability among intended users. Further studies are needed to evaluate its acceptability, implementation feasibility, effectiveness, and broader applicability.